ANTIOXIDATIVE ACTIVITY OF SUPEROXIDE DISMUTASE IN BLOOM FORMING CYANOBACTERIA - ARCHANA TIWARI; ANJALI THAKUR (International Journal of Pharma and Bio Sciences, 2013)
Cyanobacteria are autotrophic prokaryotes with excellent antioxidative system that scavenges reactive oxygen species produced during photosynthesis. Superoxide dismutase (SOD) represent the primary defence against oxygen damage. The antioxidative activity of SOD enzymes was determined in cultures of the bloom forming cyanobacteria Anabaena variabilis and Synechococcus elongates. Experimental results depict higher antioxidative activity of SOD enzyme in S. elongates than A. variabilis. The isozymes of SOD in A. variabilis and S. elongates cultures were assayed by negative staining. Two bands were visualised in S. elongates, while one band was seen in A. variabilis. The activity of these bands was insensitive to 2 mM KCN but disappeared when 30% H2O2 was added to the activity staining solutions. Because Fe-SOD is insensitive to KCN but sensitive to H2O2, the bands present were of Fe-SOD. Growth analysis and Pigment profile of cultures was also studied. Screening cyanobacteria for SOD activity can help us in exploring the immense potential of this enzyme as therapeutic enzyme drug.